Moderators of the Association Between Serum Parathyroid Hormone and Metabolic Syndrome in Participants with Elevated Parathyroid Hormone: NHANES 2003–2006 - Chen, Liang; Pei, Jian-Hao; Kuang, Jian (Hormone and Metabolic Research, 2020)
This cross-sectional study extracted data of 392 NHANES participants with elevated serum parathyroid hormone (PTH) concentrations from 2 cycles of the US National Health and Nutrition Examination Survey (NHANES) 2003–2006 and evaluated the association between serum (PTH) concentration and metabolic syndrome (MetS) to identify dietary and lifestyle factors that may modify that association. The primary outcome was MetS severity scores. Results of univariate linear regression analyses revealed that serum PTH concentrations correlated positively and significantly with MetS severity scores (β=0.399, p=0.030). After adjusting for gender, age, race, and alcohol consumption, results of multivariate analysis revealed that increased serum PTH concentration correlated significantly with higher MetS severity scores (β=0.413, p=0.045) in participants with moderate physical activity over the past 30 days. Serum PTH concentration also correlated significantly with higher MetS severity scores in participants with serum 25-hydroxyvitamin D deficiency (β=0.456 and p=0.014), those without vitamin D supplementation (β=0.524, p=0.028) and with higher protein intake (β=0.586 and p=0.030). In conclusion, increased serum PTH concentration is associated with higher MetS severity scores in participants with elevated serum PTH at baseline. The association between PTH concentration and MetS severity is moderated by participants’ physical activity levels, status of serum vitamin D, vitamin D supplementation, and daily protein intake.
Keywords: parathyroid hormone; hyperparathyroidism; dietary and lifestyle factors; metabolic syndrome; National Health and Nutritional Examination Survey